Recovery of wild Pacific oyster, Crassostrea gigas in terms of reproduction and gametogenesis two-years after the Hebei Spirit Oil Spill Accident off the West Coast of Korea. (1st December 2015) - Mondol, Mostafizur Rahman; Keshavmurthy, Shashank; Lee, Hee-Jung; Hong, Hyun-Ki; Park, Heung-Sik; Park, Sang-Rul; Kang, Chang-Keun; Choi, Kwang-Sik
Abstract: The Hebei Spirit oil spill in December 2007 at Taean off the west coast of Korea was the largest oil tanker accident in Korea. However, the impact of the spill on physiology of benthic animals remains largely unknown. Two-years after the accident, we compared reproductive effort and annual gametogenesis of the wild Pacific oyster Crassostrea gigas, residing at oil spill site with a control oyster population in Incheon Bay, North-West coast of Korea. Results showed that the oyster sampled from the oil spill site showed a significantly higher (279.0 mg standard animal − 1, P <0.05) growth by tissue dry weight to that of the control population (228.0 mg standard animal − 1, P <0.05). Histology revealed that there was no significant difference in the annual gametogenic pattern between the two populations, and most of the females of both populations spawned between August and September. During spawning season, egg mass of oysters determined using enzyme-linked immunosorbant assay (ELISA) in the oil spill area was significantly higher (136.3 mg standard animal −1, P <0.05) than the control population (120.5 mg standard animal −1, P <0.05). The tissue protein level in the oysters at the contaminated area was significantly higher (102.6 mg standard animal − 1, P <0.05) than the level measured from the control oysters (81.4 mg standard animal − 1, P <0.05). The observed better biological performances of oysters at the contaminated site suggested their recovery of the physiological status to normal level after two years of the oil spill accident. Highlights: We examined reproduction of oysters 2 years after Hebei Spirit oil spill accident. Oysters at the oil spill cite produced more eggs and higher level of carbohydrate. Better reproductive status of oyster at spill site suggested physiological recovery.